Geopolitical Uncertainty and Spending Behavior: Examining the Roles of Consumer Risk Perception, Coping Appraisal, and Resilience - Auruškevičienė, Viltė; Survilaitė, Eimantė; Misiūnas, Dalius; Reardon, Joseph (Organizations and Markets in Emerging Economies, 2025)
Nowadays consumers increasingly navigate uncertainties arising from cross-border conflicts, commercial tensions, and political instability, which pose threats not only to their mental well-being but also financial security. While existing research documents shifts in spending patterns and increased price sensitivity during geopolitical uncertainty, the psychological mechanisms driving these changes remain underexplored. This study applies Protection Motivation Theory (PMT) to examine how psychological factors shape spending patterns during periods of geopolitical uncertainty, with particular attention to the moderating role of individual resilience. Using structural equation modeling (SEM) on survey data from 1000 Lithuanian consumers, we find that both threat appraisals (perceived vulnerability and severity) and coping appraisals (self-efficacy and response efficacy) significantly influence conservative spending behaviors. Notably, individual resilience buffers the impact of perceived vulnerability on spending patterns and enhancing both response and self-efficacy. Our findings advance understanding of consumer responses to geopolitical uncertainty in three ways: by providing a theoretical framework for individual-level psychological responses, identifying resilience as a key moderating factor, and offering insights from a smaller economy’s perspective. These results have important implications for policymakers and businesses seeking to maintain economic stability during periods of geopolitical turbulence.